What is the order of the steps to solve for x in the equation 3x - 6x - 7 = 29?
Use the addition property of equality.
Use the division property of equality.
Combine like terms.

Respuesta :

Answer:

3x - 6x - 7 = 29 Given

-----------------------------------

3x - 6x -7  = 29

           + 7   + 7     Addition property of equality

3x - 6x = 36

--------------------------------------------------------------

3x - 6x = 36

(3x + -6x) = 36         Combine like terms

-3x = 36    

--------------------------------------------------------------

-3x = 36

(-3x = 36)/ -3         Division property of equality

x = -12

Step-by-step explanation:

I tried to seperate the steps so you can go through them. First you had to add on both sides to take out the like terms, then combine the 3x and the  -6x to make -3x (easier to look at and divide), and finally divide to find X. the end product using X cannot be a negative because its a filler space for a real number.

Hope this helps :)

Answer:

answer in picture

Step-by-step explanation:

Ver imagen kristentylerr1